Perjuangan Perempuan: Sumber Garapan Dalam Karya Tari Gades Bekendak Berejo - Lestari, Silvi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The story Gades Bekendak Berejo describes the struggle of three women, Risa, Lela, and Ani, who live on the banks of the Musi River. They struggle through hard work and friendship to achieve their respective dreams, despite facing many challenges. Through the discovery of an unexpected treasure, they are tested by the temptation of instant riches that almost destroys their friendship. However, the realization that true struggle and the value of friendship are the keys to success led them to the decision to reject these treasures and continue fighting. The dance work Gades Bekendak Berejo uses Sal Murgiyanto’s theory of Choreographic Structure which explains the importance of structure in dance productions, starting from processing themes, motifs, to organizing movement, space, time and energy to compose movements that reflect the storyline starting from the friends’ hard work to their moral dilemma when finding treasure. The dance work Gades Bekendak Berejo tells a story as a representation of women’s strength in facing life’s trials. The use of fishing nets in this dance emphasizes the importance of loyalty to dreams and the power of cooperation in achieving success. With a cultural background in Palembang, this dance explores the role of women in maintaining the values of loyalty, hard work and solidarity. This research aims to analyze how these story elements are translated into dance movements, with a focus on the concepts of struggle, independence and togetherness.